Functional Verification and Prognostic Value of Neutrophil Extracellular Trap-Related Genes in Pancreatic Cancer Progression - Jiaxin Xu; Liying Tu; Lijing Ma; Qisheng Tang; Yu Cao; Lihong Jiang (Frontiers in Bioscience-Landmark, 2025)
Background: Pancreatic carcinoma (PC), a severely malignant neoplasm of the digestive system, is characterized by an unfavorable prognosis. Neutrophil extracellular trap (NETosis) is a neutrophilic inflammatory form of cell death. However, it is still unknown how they relate to one another. This study aims to explore the part NETosis plays in the onset and progression of pancreatic cancer. Methods: Expression and clinical data for patients with pancreatic carcinoma were obtained from publicly accessible databases. Multigene features were constructed using the least absolute shrinkage and selection operator (LASSO). Bioinformatics analysis was combined with in vitro experiments to determine the relevant mechanism. Results: Seventeen NETosis-related genes were identified. LASSO analysis finally led to the generation of six gene characteristics, which were divided into two clusters according to the expression level. The survival outcomes of the high- and low-risk groups differ significantly, and their predictive performance is good (p < 0.05). Drug sensitivity analysis confirmed that the high-risk cohort could benefit more from 5-fluorouracil, gemcitabine, and epirubicin (p < 0.01). Using survival analysis and single-cell binding quantitative real-time polymerase chain reaction (RT-qPCR), the crucial gene LGALS3 was identified (p < 0.0001). In vitro experiments demonstrated that inhibiting LGALS3 expression may significantly decrease the proliferation and movement of PANC-1 and SW1990 cells (p < 0.05). Conclusion: We established a 6-gene risk scoring model and confirmed the effect of LGALS3 on the development of PC.